Molecular docking, quorum quenching effect, antibiofilm activity and safety profile of silver-complexed sulfonamide on Pseudomonas aeruginosa. Issue 5 (28th May 2021) - Siqueira, Fallon dos Santos; Alves, Camilla Filippi dos Santos; Machado, Alencar Kolinski; Siqueira, Josiéli Demétrio; Santos, Thiago dos; Mizdal, Caren Rigon; Moreira, Kelly Schneider; Teixeira Carvalho, Diogo; Bonez, Pauline Codernonsi; Urquhart, Carolina Gonzalez; Santos, Roberto Christ Vianna; Sagrillo, Michele Rorato; et al.
Abstract: Microbial infections caused by sessile microorganisms are known to be a more challenging issue than infections caused by the same microorganisms in the planktonic state. Pseudomonas aeruginosa is an opportunistic pathogen and biofilm-forming agent. This species presents intense cellular communication mediated by signaling molecules. This process is known as quorum sensing (QS) and induces the transcription of specific genes that favors cell density growth and three-dimensional bacterial grouping. In this context, the discovery of compounds capable of inhibiting the action of the QS signaling molecules seems to be a promising strategy against biofilms. This work aimed to evaluate the anti-biofilm action and the in vitro safety profile of a sulfamethoxazole-Ag complex. The results obtained indicate potential anti-biofilm activity through QS inhibition. In silico tests showed that the compound acts on the las and pqs systems, which are the main regulators of biofilm formation in P. aeruginosa . Additionally, the molecule proved to be safe for human peripheral blood mononuclear cells.